2019
DOI: 10.1609/aaai.v33i01.33019876
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of State Abstraction for Reinforcement Learning

Abstract: Reinforcement learning presents a challenging problem: agents must generalize experiences, efficiently explore the world, and learn from feedback that is delayed and often sparse, all while making use of a limited computational budget. Abstraction is essential to all of these endeavors. Through abstraction, agents can form concise models of both their surroundings and behavior, supporting effective decision making in diverse and complex environments. To this end, the goal of my doctoral research is to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Abstraction in DRL has gained more attention in recent years. Abel presented a theory of abstraction for DRL in his dissertation and concluded that learning on abstraction can be more efficient while preserving near-optimal behaviors [1]. Abel's abstraction theory is focused on the systems with finite state space for learning efficiency.…”
Section: Abstraction and State Discretization In Drlmentioning
confidence: 99%
See 1 more Smart Citation
“…Abstraction in DRL has gained more attention in recent years. Abel presented a theory of abstraction for DRL in his dissertation and concluded that learning on abstraction can be more efficient while preserving near-optimal behaviors [1]. Abel's abstraction theory is focused on the systems with finite state space for learning efficiency.…”
Section: Abstraction and State Discretization In Drlmentioning
confidence: 99%
“…Provided that a set of properties are predefined for a target DRL system to develop, our framework trains the system and verifies it against the properties in every iteration. To overcome the verification challenges in DRL systems, for the first time, we propose a novel approach in our framework to train the systems on a finite set of abstract states, based on the observation that approximate abstractions can still preserve near-optimal behavior [1]. These states are the abstractions of the actual states.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, algorithms like MuZero and its predecessors [Silver et al, 2017, Oh et al, 2017, Schrittwieser et al, 2020 never approximate reward functions and transition models with respect to the raw image observations generated by the environment, but instead incrementally learn some latent representation of state upon which a corresponding model is approximated for planning. This philosophy is born out of several years of work that elucidate the important of state abstraction as a key tool for avoiding the irrelevant information encoded in environment states and addressing the challenge of generalization for sample-efficient reinforcement learning large-scale environments [Whitt, 1978, Bertsekas and Castañon, 1989, Dean and Givan, 1997, Ferns et al, 2004, Jong and Stone, 2005, Li et al, 2006, Van Roy, 2006, Ferns et al, 2012, Jiang et al, 2015, Abel et al, 2016, 2018, Dong et al, 2019, Du et al, 2019, Arumugam and Van Roy, 2020, Misra et al, 2020, Agarwal et al, 2020, Abel et al, 2020, Abel, 2020, Dong et al, 2021. In this section, we briefly introduce a small extension of VSRL that builds on these insights to accommodate lossy MDP compressions defined on a simpler, abstract state space (also referred to as aleatoric or situational state by Lu et al [2021], Dong et al [2021]).…”
Section: Greater Compression Via State Abstractionmentioning
confidence: 99%
“…Abstract representation of action was useful for our HRL models only because of a third component we identified as necessary for immediate acquisition of novel behaviours: state abstraction (Abel, 2019;Andre & Russell, 2002;Botvinick et al, 2009;Radulescu, Niv, & Ballard, 2019). We allowed our most complex HRL model (model 4: abstract hierarchical) to generalise whatever it learned from one context to other relevant contexts.…”
Section: State Abstractionmentioning
confidence: 99%